Organs and Organ Music in Victorian Synagogues: Christian Intrusions or Symbols of Cultural Assimilation? - Hillsman, Walter (Studies in church history, 1992)
The rise and decline of organs in British synagogues from about 1850 to the present day is intrinsically linked to social, political, and religious developments. It therefore provides a fascinating focus for studying some of the complexities of change in Anglo-Jewry, the extent to which Victorian British Jews were affected by developments in Judaism elsewhere, and the adoption of, and reaction against, certain cultural phenomena perceived by Jews as Christian.